Analysis Of The Application Of The Transport Model With Least Cost Method (case study at PT.SI) - Agung Firdausi Ahsan; Budyi Suswanto; Emon Rifa’i (Technium: Romanian Journal of Applied Sciences and Technology, 2023)
Transport problems related to the distribution of goods and services from various production centers to several points of sale. Distribution plays an important role because without the right distribution model, the distribution process can take a high cost and a relatively long time. In this study using the least cost method where its use is based on rules or normative allocation of supply and resource needs in a transport matrix without calculating the economic magnitude, from the results of this study, the cost of Minimum shipment is IDR 325,050,000 with consolidated delivery as follows because Tangerang factory ships to Balikpapan, Cirebon and Palembang cities. For Karawang factory to send products to Jakarta city, Surabaya, Bali, Yogyakarta and Cirebon Meanwhile, the Sidoarjo factory ships products to the cities of Surabaya and Makassar.